An analysis of interaction design features in virtual reality applications - Mohamed Yusoff, Haris; Mohd Lazim, Nur Aniza; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Virtual reality technology has come a long way but many VR systems still struggle to offer smooth and natural interactions that feel truly immersive. This study explores how key design features like affordance, feedback, and challenge shape the way people experience VR across five popular applications. The findings show that engaging both the mind and body keeps users focused and involved, while realistic touch, pressure, and vibration make the virtual world feel more authentic. At the same time, we learned that giving users a sense of control and making sure their actions feel smooth and responsive are crucial for keeping them comfortable and present. Overall, this research highlights that creating great VR experiences depends on finding the right balance between immersion, ease of use, and realistic feedback. By understanding these elements, designers can make VR more intuitive, enjoyable, and truly engaging for everyone.